Useful Functional Outcome Can be Achieved after Motor Nerve Transfers in Management of the Paralytic Hand. An Observational Study. Issue 1 (February 2016) - Sallam, Asser A.; El-Deeb, Mohamed S.; Imam, Mohamed A.
Background: Nerve transfers have demonstrated encouraging outcomes in peripheral nerve reconstructions compared with the conventional direct repair or grafting. Questions/Purposes: We aimed to identify whether the patient's demographics, delay to surgery, degree of loss of grip and pinch strengths, mechanism of injury, and compliance to hand therapy have an impact on the functional outcome of motor nerve transfers in patients with paralytic hand. Methods: Fifty-five patients with a mean age of 31.05 (18–48) years with complete isolated high injuries of radial, ulnar, and median nerves, who underwent motor nerve transfers, were reviewed. The outcome was assessed using the Medical Research Council (MRC) scale and measurement of grip and pinch strengths of the hand at minimum 1-year follow-up (mean of 14.4 (12–18) months). Patient's age and gender, delay to surgery, body mass index (BMI), degree of loss of grip and pinch strengths, educational level, occupation, mechanism of injury, and compliance to hand therapy were analyzed to determine their impact on the extent of recovery of hand function. Results: Forty of fifty five (72.73%) patients regained useful functional recovery (M3–M4) with satisfactory grip hand functions. Worse motor recovery was observed in older ages, delayed surgical intervention, higher BMI, and greater postoperative loss of grip and pinch strengths in comparison to the healthy opposite hand. Better outcomes are significantly associated with higher educational level and postoperative compliance to hand therapy. Contrarily, there was no significant association between gender, occupation, mechanism of injury, and achievement of useful functional recovery. Conclusions: Successful nerve transfers are expected with experienced skilled surgeons. However, outstanding outcomes are not the standard, with about one fourth failing to achieve M3 grade. The educational level, hand dominance, compliance to hand therapy, loss of grip and pinch strengths, age, injury-surgery interval, and BMI are possible predictors of patients' outcome.